2015
DOI: 10.1039/c5ta04802h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of robust superhydrophobic surfaces by modification of chemically roughened fibers via thiol–ene click chemistry

Abstract: Superhydrophobic fabrics were fabricated by creation of roughening structures through alkali etching of fibers, modification with mercapto silanes and hydrophobization via thiol–ene click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(81 citation statements)
references
References 64 publications
3
77
1
Order By: Relevance
“…To establish chemical bonds on fiber, a pretreatment process was employed. For example, Xue et al hydrolyzed the surface of poly(ethylene terephthalate) (PET) fabric in an alkaline condition. The NaOH hydrolysis of PET breaks down the ester links leading to the formation of hydroxyl and carboxylic groups.…”
Section: Durability and General Improvement Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish chemical bonds on fiber, a pretreatment process was employed. For example, Xue et al hydrolyzed the surface of poly(ethylene terephthalate) (PET) fabric in an alkaline condition. The NaOH hydrolysis of PET breaks down the ester links leading to the formation of hydroxyl and carboxylic groups.…”
Section: Durability and General Improvement Strategiesmentioning
confidence: 99%
“…d) SEM images of 1: pristine PET, 2: E‐PET, 3: E‐PET‐SH, and 4: E‐PET‐S‐F fabrics. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Durability and General Improvement Strategiesmentioning
confidence: 99%
“…38,149 At present, research about special wettability materials for oil/water separation has attracted much interest of scientific workers and has been reported in many publications. 23,32,38,39,51,80,113,145,150154 As a typical example, Jiang et al prepared the superhydrophobic and superoleophilic Teflon-coated mesh for oil/water separation for the first time in 2004. 153 Since then novel functional surfaces with extreme wettability have been widely investigated.…”
Section: ¹2mentioning
confidence: 99%
“…are all often used as modification materials. Inspired by perfect special wettability in nature, various kinds of superhydrophobic surfaces have been fabricated for practical applications, including anticorrosion metals, 9,37 waterproof fabrics, 23 sponges and meshes or other hard substrates for oil/water separation, 36,3840 self-cleaning surfaces, 4144 and so on. To achieve some practical applications, superhydrophobicity has been combined with other performance to achieve multifunctional materials such as responsive materials, 45 transparent superhydrophobic surfaces, 46 and selfhealing superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Li has done a series of studies on oil-water separation materials in harsh conditions [35], such as fabricating superhydrophobic CS and silica overlap coated meshes for efficient oil-water separation. Xue et al [36] reported superhydrophobic polyester fabrics obtained through alkali etching, chemical vapor deposition, and ultraviolet light initiated click chemistry. Unfortunately, the component toxic fluorinated materials may cause great harm to the environment.…”
Section: Introductionmentioning
confidence: 99%